SULUK SYEIKH MAJNUN (NILAI SUFISTIK DALAM TRADISI KLASIK PESISIRAN) - M. Mudlofar (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This study aimed to describe the mystical values found in the classical manuscript of "Suluk Sheikh Majnun", which were classified as mystical manuscripts of coastal Javanese literature. The research method is executed with a descriptive qualitative approach. Besides that this study also employed the objective and aesthetic approach. Objective approach is grounded in the text and is not connected to the other aspects that are outside the text. Specifically, the aesthetic approach used in this study was the aesthetic of Al Ghazali mystic. Mystical aesthetics associated with achieving the essentials happiness. The data of this research was written data. Data is written in the form of guru gatra, guru wilangan, guru lagu, words, and sentences that reflect the structure of the text, the mystical values of the text, and functions of the text contained within the object of research. The values ​​contained in Suluk Sufi Sheikh Majnun include; (1) al imaanu (faith), (2) al taubatu (consciousness), (3) al shabru (patience), (4) al zuhdu (asceticism), (5) al ikhlaasu (sincerity), (6) al tawakkalu (resignation), (7) al mahabbatu (love), (8) al kamalu (perfection) (9) al ma'rifatu (knowing), and (10) al ridla (willingness). The values ​​in Suluk Sheikh Majnun are the beauty of the Allah swt, the Almighty God’s, characters, which show His love and affection.